2019
DOI: 10.1590/1984-0462/;2019;37;3;00013
|View full text |Cite
|
Sign up to set email alerts
|

KTK Motor Test: Review of the Main Influencing Variables

Abstract: Objective: To analyze the scientific literature regarding the effects of external variables on KTK motor test scores and to verify which motor tests are associated with KTK.Data sources: Four databases (PubMed, Science Direct, Scientific Electronic Library Online - SciELO - and Latin American and Caribbean Health Sciences Literature - LILACS) were used to search for studies in which the descriptors Körperkoordinationstest für Kinder and KTK were presented in the title, abstract and keywords. Inclusion criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
(54 reference statements)
0
6
1
2
Order By: Relevance
“…Overweight/obesity has a negative effect on tasks where the body is projected or moved through space (Malina et al, 2004); hence, children with overweight/ obesity have more difficulties with weight-bearing tasks because a greater proportion of excess mass has to be supported in comparison with normal-weight children (D'Hondt et al, 2009). A review by Nascimento of the KTK test found children's BMI had a strong influence on KTK test scores and that BMI had greater influence on the KTK test scores than regular practice of physical activities (Nascimento et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Overweight/obesity has a negative effect on tasks where the body is projected or moved through space (Malina et al, 2004); hence, children with overweight/ obesity have more difficulties with weight-bearing tasks because a greater proportion of excess mass has to be supported in comparison with normal-weight children (D'Hondt et al, 2009). A review by Nascimento of the KTK test found children's BMI had a strong influence on KTK test scores and that BMI had greater influence on the KTK test scores than regular practice of physical activities (Nascimento et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, both groups showed an increase of coordinative abilities after the intervention period. These results suggested that both types of intervention were effective to improve motor coordination components such as rhythm, laterality, agility, balance, and strength [ 49 ]. However, the efficacy of a wide range of qualitative coordination demands for children’s coordination development was demonstrated by the greater increase in balance beam, jumping laterally and shifting platforms tests of the EO group [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Além da composição corporal, como dito anteriormente, a prática regular de atividades físicas apresenta influência clara nos resultados do teste KTK (Nascimento et al, 2019). A prática regular de atividades físicas promove a manutenção da força e elasticidade muscular normais, o que possibilita a realização coordenada dos movimentos.…”
Section: Discussionunclassified
“…A coordenação motora está favoravelmente associada a marcadores de saúde, como atividade física, condicionamento cardiorrespiratório, força muscular, resistência e estado de peso saudável durante toda a infância. As duas principais variáveis que influenciam o desempenho motor no teste KTK são fatores antropométricos e a prática de atividades físicas (Nascimento et al, 2019) Visto que o teste KTK é um dos testes mais utilizados para avaliar coordenação motora de crianças, e sabendo que não existe na literatura uma revisão focada em analisar a relação entre coordenação motora e as duas principais variáveis que influenciam o desempenho motor no teste KTK, os objetivos desta revisão sistemática são identificar o que tem sido publicado a respeito da utilização do teste KTK nos últimos anos para avaliação da coordenação motora de crianças, e secundariamente analisar a relação entre coordenação motora, antropometria e desempenho.…”
Section: Introductionunclassified